Głos Łodzi . pismo Regionalnej Komisji Wykonawczej NSZZ "Solidarność", no. 3, 1984 - Popiełuszko, Jerzy; Katarasiński, Jerzy; Lerski, Witold ([s.n.], 1984)
Creation and circulation: W 1989 r. published legally titled Głos Solidarności